First 2-year experience of nationwide newborn screening for severe forms of T and B cell immunodeficiency: 2.3 million newborns analyzed using TREC and KREC in Russia - Marakhonov, Andrey; Mukhina, Anna; Efimova, Irina; Balinova, Natalia; Ampleeva, Maria; Bobreshova, Anastasia; Rodina, Yulia; Pershin, Dmitry; Zabnenkova, Viktoriia; Ryzhkova, Oxana; Markova, Zhanna; Shilova, Nadezhda; et al. (Frontiers in Immunology, 2026)
IntroductionHere, we present the results of a nationwide newborn screening (NBS) program in Russia, covering over 2.3 million newborns and employing TREC and KREC quantification to improve the identification of severe forms of T and/or B cell immunodeficiencies and enable early treatment initiation.MethodsA two-tier PCR testing strategy was used to define the screen-positive cohort, followed by confirmatory flow cytometry and genetic diagnostics, including fluorescent in situ hybridization (FISH) and whole-exome sequencing (WES).ResultsA total of 191 patients were diagnosed with defined forms of primary immunodeficiencies (PID), encompassing several groups of inborn errors of immunity (IEI): severe combined immunodeficiency (SCID), agammaglobulinemia, combined immunodeficiency less severe than SCID, and syndromic forms of PID. The overall birth prevalence of severe forms of T and/or B cell immunodeficiencies was 1 in 12,298 live births (95%CI: 1:10,672–1:14,247), corresponding to 8.13 cases per 100,000 newborns (95%CI: 7.02–9.37). Although the positive predictive value of KREC-based screening was relatively low, its use enabled the detection of a substantial proportion of patients with syndromic forms of PID, including Nijmegen breakage syndrome and ataxia–telangiectasia, along with various forms of agammaglobulinemia. Interestingly, 16% of diagnosed newborns had a positive family history, often with previously undiagnosed affected siblings or parents. Additionally, a considerable number of newborns detected by NBS presented with syndromic disorders not currently classified as IEI, suggesting potential avenues for future expansion of the IEI list.DiscussionImportantly, early diagnosis through NBS allowed for the timely initiation of disease-specific treatments, including hematopoietic stem cell transplantation (HSCT), immunoglobulin replacement therapy, and targeted immunosuppressive or supportive care strategies. Early intervention may reduce the risk of severe infections, improve neurodevelopmental outcomes, and prevent irreversible organ damage or malignancies in predisposed syndromes. Overall, our study demonstrates the effectiveness of large-scale implementation of TREC/KREC-based NBS in identifying a broad spectrum of immunodeficiencies and highlights future directions for improving NBS algorithms, follow-up protocols, and individualized medical management for affected infants.